2012
DOI: 10.1371/journal.pone.0034802
|View full text |Cite
|
Sign up to set email alerts
|

An Indirect Cue of Predation Risk Counteracts Female Preference for Conspecifics in a Naturally Hybridizing Fish Xiphophorus birchmanni

Abstract: Mate choice is context dependent, but the importance of current context to interspecific mating and hybridization is largely unexplored. An important influence on mate choice is predation risk. We investigated how variation in an indirect cue of predation risk, distance to shelter, influences mate choice in the swordtail Xiphophorus birchmanni, a species which sometimes hybridizes with X. malinche in the wild. We conducted mate choice experiments to determine whether females attend to the distance to shelter a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 56 publications
2
22
0
Order By: Relevance
“…Consistent with predictions of theoretical models, empirical studies have revealed that the female mate sampling tactic is influenced by the costs of searching [21,27-31] as well as the variation in quality among potential males [32-35]. Females should become choosier with an increase in benefits and a decrease in costs [36,37].…”
Section: Introductionmentioning
confidence: 91%
“…Consistent with predictions of theoretical models, empirical studies have revealed that the female mate sampling tactic is influenced by the costs of searching [21,27-31] as well as the variation in quality among potential males [32-35]. Females should become choosier with an increase in benefits and a decrease in costs [36,37].…”
Section: Introductionmentioning
confidence: 91%
“…One study has tested for predator effects on mate preference in sympatric males and found that male sailfin mollies (Poecilia latipinna) were less discriminating against heterospecific Amazon mollies (Poecilia formosa) in the presence of a predator than in the absence of a predator [30]. Another study found that distance from a shelter (which may be indirectly related to predation risk) increased the likelihood that swordtail females (Xiphophorus birchmanni) would mate with heterospecifics [31]. This dearth of studies on female preference is surprising given that female conspecific mate preference is the main barrier to hybridization in many species [32] and females generally invest more in each mating than males [33].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, females may adjust their choosiness based on their ability to afford perceived search costs. Many studies have manipulated the costs of choosiness and have found that females adjust choosiness in response to changes in a variety of factors such as parasitism (Beckers & Wagner, 2013), age (Richard, Lecomte, De Fraipont, & Clobert, 2005;Ronald, Fern andez-Juricic, & Lucas, 2012), body condition and diet (Hebets, Wesson, & Shamble, 2008;Moskalik & Uetz, 2011;Vitousek, 2009), predation (Karino, Kuwamura, Nakashima, & Sakai, 2000;Willis, Rosenthal, & Ryan, 2012), male density and trait variability (Fowler-Finn & Rodríguez, 2012a;Lehmann, 2007), and previous experiences with certain male phenotypes (FowlerFinn & Rodríguez, 2012b;Hebets, 2003;Wagner, Smeds, & Wiegmann, 2001). …”
mentioning
confidence: 99%